Revitalization of Local Wisdom in Religious Moderation - Habibi, Ibnu (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
This study aims to examine the practice of multi-religious tolerance in Kolong Village, Ngasem-Bojonegoro, and its relevance to the concept of religious moderation in facing the challenges of the Society 5.0 era. The research method is qualitative with a case study approach, through interviews, observations, and documentation. The results of the study are: (1) the local wisdom of Kolong Village functions as a medium for internalizing the value of tolerance from an early age, (2) the practice of tolerance is in line with the principle of religious moderation in Islamic science, namely rejecting extreme attitudes and prioritizing balance, and (3) the harmony model in Kolong Village has the potential to be revitalized to answer the challenges of globalization, digitalization, and social disruption in the Society 5.0 era. Thus, local wisdom functions to maintain social harmony while also being a reference for global peace based on Islamic values ​​rahmatan lil-‘alamin. This study contributes to developing a model of community-based religious moderation rooted in local wisdom to face the challenges of digital civilization.